ACUTE ASPECTS OF TAX REGULATION DURING CRISIS - Svetlana A. Grebenyuk (Plekhanov Russian University of Economics, 2017)
The article discusses ways of raising efficiency of the taxation mechanism through searching for variants of effective tax regulation. It is well-known that tax policy is an integral part of economic policy of any country. Increasing role of taxes in today's society, importance of developing and efficient functioning of the taxation system as a principal element of market economy stipulate the important role of taxation policy of state. The author diagnoses functions of the taxation mechanism of Pridnestrovya, studies new tools capable of influencing the dynamics of tax entering with full use of the existing potential of enterprises and organizations.